FAKTOR LINGKUNGAN YANG BERHUBUNGAN DENGAN DIARE PADA ANAK BALITA DI DESA HAJIMENA KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN TAHUN 2019 - Prabaswara, Danuja (Poltekkes Kemenkes Tanjung Karang, 2021)
The diarrhea morbidity rate in the working area of the Hajimena Health Center tends to increase from year to year. During the last two years, the highest incidence of diarrheal disease was in the 1-4 year age group. This study aims to determine the relationship between environmental factors and the incidence of diarrhea in children under five. This study used a cross-sectional design. The research population was all children under five (1-5 years) in Hajimena Village, South Lampung Regency, 1,052 people. The sample in this study was 101 toddlers who were selected randomlyâ€”collecting data by observation and interviews. Data analysis was carried out univariate and bivariate using the Chi-Square test. The results of this study indicate a significant relationship between diarrhea in children under five with waste disposal facilities (p-value = 0.010) and waste water disposal facilities (p-value = 0.001). Meanwhile, clean water facilities and family latrine facilities, in this study, did not show a significant relationship. Increased knowledge and skills of the community in managing household waste is needed in an effort to reduce the incidence of diarrhea in children under five.Â